Women in Budgeting: A Critical Assessment of Participatory Budgeting Experiences - Allegretti, Giovanni (2016)
Budgeting has for too long been considered a technical arena for highly skilled elites. Participatory Budgeting (PB) opens up the field and creates a space for local communities to discuss the equitable distribution of resources. However, gender has not been at the forefront of the PB debate. On the other hand, gender responsive budgeting has had its own growth trajectory, often not including participatory methods. The chapter highlights possible intersections between PB and gender mainstreaming and notes PB’s potential in addressing issues of gender mainstreaming and social justice, following dialogues with other complementary democratic innovations.